TAHLIL SEBUAH SENI RITUAL KEMATIAN PADA KEPERCAYAAN ISLAM JAWA Tinjauan Teks dalam Konteks - Soerjo Wido Minarto (Gelar : Jurnal Seni Budaya, 2011)
Tahlil is an praying activity jointly prayer by a Muslim group of NU Ahlussunnah wal jamaah. The goal is for the ritual of death is usually done at certain times after a person’s death, such as 3, 7, 40, 100, 1000 day and so on. Considering from his form and medium, tahlil is the art of symbols and rituals that have meaning in the context of the text. Key words : tahlil, Islamic ritual art, death ritual.